The Rise of Computer Based Assessment: The Future of Educational Evaluation in Indonesia - Haryadi, Rofiq Noorman (Universitas Negeri Makassar, 2025)
In the evolving landscape of Indonesian education, the shift towards computer-based assessment (CBA) marks a significant transformation, heralding new prospects for educational evaluation. This transition is propelled by the increasing integration of digital technologies in education, aligning with global trends and responding to the burgeoning need for efficient, scalable, and innovative assessment methods. The backdrop of this research is Indonesia's endeavor to enhance educational outcomes and align assessment practices with the demands of the digital age. Through a qualitative lens, this study explores the potential of CBA to redefine educational evaluation in Indonesia, examining its implications, challenges, and opportunities from the perspectives of educators, students, and policymakers. The research uncovers that while CBA offers numerous advantages, including immediate feedback, enhanced test security, and logistical efficiency, its implementation is fraught with challenges. These include infrastructure readiness, digital literacy among stakeholders, and concerns regarding the validity and fairness of assessments. Furthermore, the study delves into the pedagogical shifts necessitated by CBA, emphasizing the need for alignment with instructional practices and the development of relevant digital competencies. In synthesizing these findings, the research posits that while CBA represents a promising frontier for educational assessment in Indonesia, its success hinges on strategic planning, inclusive policy-making, and capacity building, ensuring that it effectively supports learning and teaching in the digital age.